Investigating Interest and Necessity: A Phenomenological Analysis of Generation Z's Involvement in Islamic Religious Education - Jannah, Nurul; Damni, Albertos (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
This study examines the importance and value of Islamic Religious Education for university students, with particular attention to the relationship between personal interest and the necessity of spiritual and moral development in higher education. Using a qualitative phenomenological approach, data were collected through semi-structured interviews, observations, and documentation involving students from diverse academic backgrounds. The data were analyzed using Interpretative Phenomenological Analysis (IPA) to capture students’ lived experiences. The findings indicate that religious education is not merely perceived as a compulsory subject, but is experienced as a meaningful process that contributes to character formation, moral development, and life balance in the context of rapid technological change. Students’ engagement emerges through the interaction between internal factors, such as personal beliefs, and external influences, including institutional environment and pedagogical practices. Importantly, the study reveals that what initially appears as an academic obligation can develop into personally significant engagement. These findings highlight the dynamic relationship between interest and necessity and suggest the need for more responsive and student-centered approaches in religious education.